Normative data and psychometric properties of the parent and teacher versions of the strengths and difficulties questionnaire (SDQ) in an Iranian community sample - Zahra Shahrivar (Journal of Research in Medical Sciences, 2009)
BACKGROUND: Strengths and difficulties questionnaire (SDQ) is a widely used instrument for screening mental problems in children and adolescents. The main aim of this study was to evaluate the validity and psychometric properties of this questionnaire in comparison with the children behavior checklist (CBCL) and psychiatric interview. METHODS: The study was done in two stages. At stage one, 600 children aged between 6 and 12 were evaluated using the parent and teacher versions of SDQ and CBCL. At stage two, 25 children with the scores above the cut point reported by the developer of SDQ and 27 children with the score below this point were selected to be interviewed by a child and adolescent psychiatrist according to Diagnostic and Statistical Manual of Mental Disorders, 4th Edition (DSM-IV) classification and by another clinician using the K-SADS-PL (Schedule or Affective Disorders and Schizophrenia for School-Age Children- Present and Lifetime Version) as a semi structured interview. RESULTS: The mean scores of SDQ subscales found in this study were comparable to what found in other studies in other countries. The cut-off points of SDQ were almost similar to that of other researches. The internal consistency and concurrent validity of this questionnaire was good. CONCLUSIONS: The current study showed that both parent and teacher versions of SDQ in Persian language can be used as a valid tool in screening the mental problems in children and adolescents. KEYWORDS: SDQ, CBCL, mental problems, children, K-SADS.